Significant and sound: US medium-range missiles in Germany - Jonas Schneider; Torben Arnold (Stiftung Wissenschaft und Politik (SWP), 2024)
At the NATO summit in July 2024, the United States and Germany announced that, in 2026, the United States would be deploying ground-launched medium-range missiles in Germany that can reach targets in Russia's heartland. This deployment is a critical step because it gives NATO new capabilities in an area that has become more important as a result of Russia's missile war against Ukraine. Moscow has threatened to respond with military countermeasures. A close analysis reveals, however, that the associated risks for Germany are less severe than many assume. The plan even has the potential to contribute to future arms control agreements with Russia.
Keywords: 320; US medium-range missiles in Germany; Nato; Tomahawk; SM 6; LRHW; Dark Eagle; Russia; arms control